THE INTERMEDIATE LEARNER’S CHOICE OF SELF-AS-A-MODEL STRATEGIES AND THE EIGHT-SESSION PRACTICE IN LEARNING OF THE FRONT CRAWL SWIM (Kinesiology, 2017)
The aim of this study was to investigate the intermediate learners’ choice of self-as-a-model strategiesfor learning the front crawl swim by extending the amount of practice. Participants (n=40) were divided intothree groups: choice (free to choose to watch a video footage of their best or overall performance anytimeduring a practice), yoked (paired to the learners of the choice group), and control group (did not watch anyvideo). Experimental design also involved a pretest, eigh tacquisition blocks, and a 48-hour retention test.The measures included a qualitative analysis of the front crawl swim and the rate of self-efficacy beliefquestionnaire. Results showed better learning of the front crawl swim for the choice group in comparison tothe yoked and control group. It was also verified that the belief of self-efficacy improved in the choice andyoked groups. Most learners chose self-observation of their overall performance during the entire practice.The rest of learners waved in their choices. Self-observation of either the best or overall performance hadsimilar effects on learning the front crawl swim. In conclusion, to provide learners with freedom of choiceduring the extended acquisition phase was positive for motor learning, regardless of whether or not therewere changes in their choices.Key words: freedom of choice, self-observation strategies, motor learning, amount of practice